Evaluation of the support of young athletes in the elite sport system - Güllich, A.; Emrich, E.; Schwank, B. (5. International Forum on Elite Sport. Beijing, China, 3-6 September 2007, 2007)
Systematic application of scientific methods in order to evaluate to what degree a programme or a measure contributes systematically to the achievement of the purpose the programme or measure is designed for. Hard core of underlying assumptions: • Long-term continuous involvement in one sport • Continuous inclusion in support system • Increment of success over involvement time • Juvenile performance and success are valid predictors for long-term success in elite sport • The construction of the support system is based on a hard core of time-economic observational assumptions • Athlete-related support measures mainly aim at extensive and/or intensive time-economy • Current concepts: Further dynamisation of time